2021
DOI: 10.1111/1541-4337.12728
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of whole grain: effects on dietary carbohydrate quality, the gut microbiome, and consequences of processing

Abstract: Grains are important sources of carbohydrates in global dietary patterns. The majority of these carbohydrates, especially in refined‐grain products, are digestible. Most carbohydrate digestion takes place in the small intestine where monosaccharides (predominantly glucose) are absorbed, delivering energy to the body. However, a considerable part of the carbohydrates, especially in whole grains, is indigestible dietary fibers. These impact gut motility and transit and are useful substrates for the gut microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 225 publications
4
53
1
Order By: Relevance
“…Accumulated data indicates that gut microbes and their metabolites are related to the course, prevention, or treatment of obesity, type 2 diabetes, ulcerative colitis, and cancer [43]. Whole grains are associated with the morbidity and mortality of many diseases, which may be due in part to the impact on the intestinal flora [44]. In the present study, PHB supplementation significantly reversed the structure and composition of the gut microbiome in HFD mice to a near-normal status (Figure 3F).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated data indicates that gut microbes and their metabolites are related to the course, prevention, or treatment of obesity, type 2 diabetes, ulcerative colitis, and cancer [43]. Whole grains are associated with the morbidity and mortality of many diseases, which may be due in part to the impact on the intestinal flora [44]. In the present study, PHB supplementation significantly reversed the structure and composition of the gut microbiome in HFD mice to a near-normal status (Figure 3F).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it can be useful to better exploit nutritional characteristics of rice varieties. In general, cereals contain carbohydrates, proteins, vitamins, minerals, antioxidants and phytochemicals [18,19]. However, attention should be paid to carbohydrate contents of different cereals and varieties and, in particular, to amylose, one of the components of starch.…”
Section: Introductionmentioning
confidence: 99%
“…In non-fermented breads, high fructan concentrations can be obtained [21]. Commonly utilized yeasts (such as Saccharomyces cerevisiae) have invertase (EC 3.2.1.26) activity, leading to partial degradation of fructan during dough mixing and fermentation [14]. Verspreet et al (2013) [168] reported an almost 80% decrease in the fructan content of bread after baking with added yeast and the losses occurred during the mixing and fermentation processes, pointing towards the enzymatic activity rather than the heat treatment as the causal factor.…”
Section: Baking Processmentioning
confidence: 99%
“…Processing involves the use of one or more-unit operations, involving application of mechanical or thermal energy, hydration and often activation of the endogenous biological enzymatic system of the grains. These operations induce various macroscopic to molecular level changes in the grain components, hence affecting the nutritional, technological and sensory properties of the products [11][12][13][14]. While fractionation causes an uneven distribution of DF both in terms of quantity and quality in resulting fractions, additional changes occur in the DF matrix during further processing even without changes in proximate composition.…”
Section: Introductionmentioning
confidence: 99%